IMPLEMENTASI ETIKA PROFESIONALISME GURU DALAM MENINGKATKAN KEPUASAN SISWA DI SMP TELKOM PEKANBARU - Adly Azka Rifqi; Fitriana Fitriana; Yenda Puspita; Azhar Azhar; Meliza Sari (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2022)
The teacher is a leader whose job is to be able to organize, monitor and direct all activities in the learning process at school. The purpose of this research is to explain how teachers apply professional ethics to increase student satisfaction at SMP Telkom Pekanbaru. This study uses a qualitative descriptive method with data collection through observation and interviews. The survey results show that teacher professional ethics can increase student satisfaction because SMP Telkom Pekanbaru teachers carry out their work as teachers professionally and satisfactorily, and the implementation is effective, this shows that things are going as expected. Teacher behavior is governed by the Teacher Professional Ethics, which reflects the noble values expressed in their actions, creates a good school atmosphere, and applies professional ethics by seeking information about students.